PEN America best debut short stories. 2018 - Igarashi, Yuka (Catapult, 2018)
"PEN America Best Debut Short Stories 2018 celebrates twelve outstanding stories by todays most promising new fiction writers and the literary magazines that discovered them. The characters within these pages include a college dropout dressed up as Hercules at Disney World; a college graduate playing a prostitute in a ghost town in Montana; a father from Trinidad leading a double life on a temporary visa; and a housewife in Taipei perfectly performing her familial and marital duties while harboring secret desires. This years selections were made by three award-winning writers, themselves innovators of the short story form: Jodi Angel, Lesley Nneka Arimah, and Alexandra Kleeman. Each work is accompanied by commentary from the editors who first published it, explaining what made the piece stand out from the submissions pile, and why they were moved to share it with readers."--provided by Amazon.com.